Axial Compression Effect on Carbonation Resistance of Fly Ash Concrete: An Experimental and Modeling Study - Li, Hu; Tian, Zhuang; Liu, Fulei; Li, Pengcheng (Asia Pacific Economic and Management Review, 2026)
To investigate the durability of fly ash concrete under service conditions, this study systematically examined the effect of axial compressive load on its carbonation resistance. Prismatic specimens of ordinary Portland cement concrete (OPC) and concrete with 30% fly ash (FAC30) were prepared. Axial compressive loads at three levels (0%, 30%, and 60% of the ultimate strength) were applied using a self-designed long-term loading device. The specimens were then subjected to accelerated carbonation for 28 days in an environment with a CO2 concentration of 20±1%, a temperature of 20±2°C, and a relative humidity of 70±3%. Carbonation depths were measured at 7, 14, and 28 days, and the distributions of internal pH value and calcium carbonate content were analyzed. The results showed that the axial load had a dual effect on the carbonation resistance of concrete. Under a low load level (30%), the carbonation depth of FAC30 decreased by approximately 6.5% compared to that of the unloaded specimens, indicating a certain inhibitory effect. However, under a high load level (60%), the carbonation depths of OPC and FAC30 increased significantly by 44.4% and 43.2%, respectively. The incorporation of fly ash substantially reduced the alkali reserve of concrete, resulting in a carbonation depth much greater than that of OPC, which was the dominant factor affecting carbonation resistance. Based on Fick's law and the experimental data, a prediction model for carbonation depth considering the axial load ratio was established as XC=X0(1+kSm). Validation showed that the predicted values agreed well with the experimental results (R2 > 0.96). This study provides an important theoretical and experimental basis for accurately predicting the service life of fly ash concrete structures under load.